Neurochemical and Cognitive Beneficial Effects of Moderate Physical Activity and Catechin in Aged Rats - Margarita R. Ramis; Fiorella Sarubbo; David Moranta; Silvia Tejada; Jerònia Lladó; Antoni Miralles; Susana Esteban (MDPI AG, 2021)
A healthy aging process is a requirement for good life quality. A relationship between physical activity, the consumption of antioxidants and brain health has been stablished via the activation of pathways that reduce the harmful effects of oxidative stress, by inducing enzymes such as SIRT1, which is a protector of brain function. We analyzed the cognitive and neurochemical effects of applying physical exercise in elderly rats, alone or in combination with the antioxidant catechin. Several tests of spatial and episodic memory and motor coordination were evaluated. In addition, brain monoaminergic neurotransmitters and SIRT1 protein levels were assessed in the brains of the same rats. The results show that physical activity by itself improved age-related memory and learning deficits, correlating with the restoration of brain monoaminergic neurotransmitters and SIRT1 protein levels in the hippocampus. The administration of the antioxidant catechin along with the exercise program enhanced further the monoaminergic pathways, but not the other parameters studied. These results agree with previous reports revealing a neuroprotective effect of physical activity, probably based on its ability to improve the redox status of the brain, demonstrating that exercise at an advanced age, combined with the consumption of antioxidants, could produce favorable effects in terms of brain health.